Analysis Dual Factor to Entrepreneurial Desirability - Sri Irdayati; Ahdia Amini (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
The primary objective of this study was to investigate the factors influencing the emergence of entrepreneurial desirability at master’s degree student. The study was conducted to verify the effect of interaction between entrepreneurial cognition (the perceived entrepreneurial self-efficacy, the perceived entrepreneurial feasibility, entrepreneurial desirability). A survey was conducted on a convenience sample of 100 master’s degree students at 2 universities namely sample A campus and sample B campus in Jakarta, Indonesia. The maximum-likelihood test was used as a structural equation modeling method to test the model. The results show, to some extent, validate the interaction between the entrepreneurial cognitive patterns. The limitations on this study, that is only provides an overview of the conditions of participants in 2 campus samples who may have different vision and mission of organizing entrepreneurship programs. Subsequent research can investigate more comprehensive patterns of interaction on the factors that influence entrepreneurial desirability by considering other variables besides variables that have carefully studied by researcher.